2005
DOI: 10.1037/0096-1523.31.6.1331
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Feedback in Music Performance: The Role of Melodic Structure and Musical Skill.

Abstract: Five experiments explored whether fluency in musical sequence production relies on matches between the contents of auditory feedback and the planned outcomes of actions. Participants performed short melodies from memory on a keyboard while musical pitches that sounded in synchrony with each keypress (feedback contents) were altered. Results indicated that altering pitch contents can disrupt production, but only when altered pitches form a sequence that is structurally similar to the planned sequence. These exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
116
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(136 citation statements)
references
References 80 publications
(151 reference statements)
12
116
8
Order By: Relevance
“…Nonpianists and pianists often respond similarly to AAF (see, e.g., Pfordresher, 2005); however, it has also been shown that musical training can enhance instrument-specific associations between actions and sound (e.g., Drost, Rieger, & Prinz, 2007). It is thus natural to wonder what effects one might find if the present paradigm were presented to pianists.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Nonpianists and pianists often respond similarly to AAF (see, e.g., Pfordresher, 2005); however, it has also been shown that musical training can enhance instrument-specific associations between actions and sound (e.g., Drost, Rieger, & Prinz, 2007). It is thus natural to wonder what effects one might find if the present paradigm were presented to pianists.…”
Section: Discussionmentioning
confidence: 86%
“…On the keyboard, the numbers 1-5 were arranged in a row above the corresponding piano keys, with arrows pointing to each key. Nonpianists typically learn this notation system with little effort (see, e.g., Pfordresher, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, learning to produce a sequence of key presses on a piano does not depend on the presence of sound, even for people without any musical training (Pfordresher, 2005, Experiment 3). Furthermore, the absence of sound during keyboard performance of a learned melody has negligible effects on trained performers (Finney, 1997;Finney & Palmer, 2003;Pfordresher, 2005;Repp, 1999;Repp & Knoblich, 2004) or untrained performers (Pfordresher, 2005). actions when auditory feedback is present, though they may not rely on the presence of feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Related effects of structural congruence on timing accuracy have been observed in studies that required auditory sequences to be produced by unimanual finger movements (e.g., Keller & Koch, 2006;Pfordresher, 2003Pfordresher, , 2005. The focus of these earlier studies was on sequential planning, and the sequences contained patterns of transitions that were complex relative to the 5 Note that set-level compatibility is determined by the overlap between the properties of a stimulus set and a response set in Kornblum's (1992;Kornblum et al, 1990) models, while our discussion concerns the overlap between a set of responses (the movement pattern) and a mixed set of distal response effects and externally controlled stimuli (the auditory goals).…”
Section: Structural Congruencementioning
confidence: 99%
“…However, the benefits of having a simple perceptual goal may in this case be tempered by structural incongruence between the auditory goal representation (consisting of a series of identical elements) and the motor program that drives movement (consisting of a series of disparate elements: left-hand taps, right-hand taps, and, presumably, intervening 'rests' that coincide with pacing signal events 2 ). Research addressing the production of musical sequences has shown that timing accuracy can be affected by whether or not structural relations between movements and their auditory effects are compatible (e.g., Keller & Koch, 2006;Pfordresher, 2003Pfordresher, ,2005. Such findings suggest that, during ABS, the benefits of integrated goal 2 Given that movement-related brain areas have been implicated in covert synchronization with rhythmic stimuli (e.g., Grahn & Brett, 2007;Oullier, Jantzen, Steinberg, & Kelso, 2005;Schubotz, Friederici, & von Cramon, 2000), it is possible that actors imagine the movement of body parts other than the hands (e.g., vocal articulators) during these rests.…”
mentioning
confidence: 99%